Oral health related quality of life among transgender women in Malaysia - Mohd, Farah Natashah; Said, Abdul Hadi; Ali, Aainaa; Lestari, Widya; Draman, Samsul; Md Aris, Mohd Aznan (2020)
Objective: Transgender women (TGW) is a unique group with many health issues related to them unexplored. For example, there is severely lacking evidence on oral health related quality of life (OHRQOL) among TGW. Therefore, this research aims to assess the OHRQOL among TGW in Malaysia and its associated factors. Materials and methods: This was a cross sectional study among 100 TGW who attended a health program in Kemaman, Terengganu, Malaysia. OHRQOL was measured using the validated Malay short version of oral health impact profile (OHIP) 14 questionnaire. Sociodemographic data, discrimination experience and oral hygiene practice were also obtained to assess for the relationship with their OHRQOL. All data were subjected to bivariate testing and further analysis using multiple logistic regression to determine factors related with poor OHRQOL. Results: The total mean OHIP score was 16.67 ± 10.39. This was higher compared to the local studies done among the general population which mean TGW have poorer OHRQOL. More interestingly, it was found that the score was comparable with those who are living with HIV/AIDS in Malaysia. Further analysis revealed that there was no statistically significant association found between the OHRQOL and other factors with p>0.05. Conclusion: TGW in our study had poorer OHRQOL compared to the general adult population and almost equivalent to those with HIV/AIDS. This showed that their oral health had a huge impact on their quality of life. All the necessary measures need to be undertaken to improve their oral health and subsequently improve their OHRQOL.